The Time in Therapeutic Range and Bleeding Complications of Warfarin in Different Geographic Regions of Turkey: A Subgroup Analysis of WARFARIN-TR Study - Salih Kılıç; Ahmet Çelik; Hüseyin Altuğ Çakmak; Abdülmecit Afşin; Ahmet İlker Tekkeşin; Gönül Açıksarı; Mehmet Erdem Memetoğlu; Fatma Özpamuk Karadeniz; Ekrem Şahan; Mehmet Hayri Alıcı; Yüksel Dereli; Ümit Yaşar Sinan; et al. (Balkan Medical Journal, 2017)
Background: The time in therapeutic range values may vary between different geographical regions of Turkey in patients vitamin K antagonist therapy. Aims: To evaluate the time in therapeutic range percentages, efficacy, safety and awareness of warfarin according to the different geographical regions in patients who participated in the WARFARIN-TR study (The Awareness, Efficacy, Safety and Time in Therapeutic Range of Warfarin in the Turkish population) in Turkey. Study Design: Cross-sectional study. Methods: The WARFARIN-TR study includes 4987 patients using warfarin and involved regular international normalized ratio monitoring between January 1, 2014 and December 31, 2014. Patients attended follow-ups for 12 months. The sample size calculations were analysed according to the density of the regional population and according to Turkish Statistical Institute data. The time in therapeutic range was calculated according to F.R. Roosendaal’s algorithm. Awareness was evaluated based on the patients’ knowledge of the effect of warfarin and food-drug interactions with simple questions developed based on a literature review. Results: The Turkey-wide time in therapeutic range was reported as 49.5%±22.9 in the WARFARIN-TR study. There were statistically significant differences between regions in terms of time in therapeutic range (p<0.001). The highest rate was reported in the Marmara region (54.99%±20.91) and the lowest was in the South-eastern Anatolia region (41.95±24.15) (p<0.001). Bleeding events were most frequently seen in Eastern Anatolia (41.6%), with major bleeding in the Aegean region (5.11%) and South-eastern Anatolia (5.36%). There were statistically significant differences between the regions in terms of awareness (p<0.001). Conclusion: Statistically significant differences were observed in terms of the efficacy, safety and awareness of warfarin therapy according to different geographical regions in Turkey